Exploring Interaction of TNF and Orthopoxviral CrmB Protein by Surface Plasmon Resonance and Free Energy Calculation - V. Ivanisenko, Nikita; V. Tregubchak, Tatiana; V. Saik, Olga; A. Ivanisenko, Vladimir; N. Shchelkunov, Sergei (Protein and Peptide Letters, 2014)
Inhibition of the activity of the tumor necrosis factor (TNF) has become the main strategy for treating inflammatory diseases. The orthopoxvirus TNF-binding proteins can bind and efficiently neutralize TNF. To analyze the mechanisms of the interaction between human (hTNF) or mouse (mTNF) TNF and the cowpox virus N-terminal binding domain (TNFBD-CPXV), also the variola virus N-terminal binding domain (TNFBD-VARV) and to define the amino acids most importantly involved in the formation of complexes, computer models, derived from the X-ray structure of a homologous hTNF/TNFRII complex, were used together with experiments. The hTNF/TNFBD-CPXV, hTNF/TNFBD-VARV, mTNF/TNFBD-CPXV, and mTNF/TNFBD-VARV complexes were used in the molecular dynamics (MD) simulations and MM/GBSA free energy calculations. The complexes were ordered as hTNF/TNFBD-CPXV, hTNF/TNFBD-VARV, mTNF/TNFBD-CPXV and mTNF/TNFBD-VARV according to increase in the binding affinity. The calculations were in agreement with surface plasmon resonance (SPR) measurements of the binding constants. Key residues involved in complex formation were identified.
Keywords: tumor necrosis factor (TNF)